Educational Pathways and Employment Stability: A Comparative Study of Vocational and University Graduates in the Tourism Sector of Northern Albania - Toma, Volfrida; Borici, Ardita (European Journal of Social Science Education and Research, 2025)
Employment stability is a key concern for young graduates entering labour markets shaped by technological change, seasonality and shifting employer expectations. The abstract explicitly integrates Human Capital Theory and Signalling Theory to establish the analytical rationale behind differences in employment stability between educational pathways. This theoretical framing clarifies the mechanisms through which vocational and university qualifications influence labour market positioning, ensuring that the study aligns with international academic debates and moves beyond a locally descriptive case. A quantitative questionnaire was administered to 230 final-year students, and stability was assessed through multiple dimensions, including job duration, contract type, career progression expectations and perceived job security. Descriptive statistics, independent-samples t-tests and regression models were used to analyze pathway differences and identify predictors of perceived stability. Findings show that university graduates associate their qualifications with higher long-term stability and advancement opportunities, whereas vocational graduates demonstrate stronger immediate employability but greater uncertainty regarding career progression. Technological readiness and training quality significantly influence stability perceptions across both groups. The study contributes to international debates on graduate transitions by illustrating how education-related competencies shape labour market expectations in tourism-dependent economies and informs policy efforts aimed at enhancing youth employability and sector resilience.